Aspects of Self-presentation in the Speeches of Isocrates - Veteikis, Tomas (Literatūra, 2014)
This article, based on the paper presented at the ISHR 2013 Conference (July 24–27, 2013, Chicago), reconsiders the rhetorical image of Isocrates, preserved in his literary works and especially in three of the most prominent speeches, Panegyricus, Antidosis, and Panathenaicus, discusses certain controversies and difficulties of determining his public character and his attitude towards the audience and, basing on both empirically gathered data (references found in Isocrates’ writings) and on the theoretical basement provided by the consideration of the classical rhetoric tradition and the modern communication science approach, reviews the main aspects of the speaker’s self-presentational tactics as seen in his self-reflexive statements (found in the mentioned speeches), the examination of which could lead to a better comprehension of the otherwise obscure picture of this influential Athenian rhetorician.